Increasing Productivity Of Traditional Health Drink - Wike Agustin Prima Dania (Journal of Innovation and Applied Technology, 2015)
ABSTRACTThe purposeofthis activityis to applymechanical machine such as washing machine for rhizome (empon-empon), gra-termachine, andhydraulicpress toimpro-ve theperformanceandefficiency of productionprocess oftraditional drinks (jamu). This activity has been done by “learning by doing” method emphasized to practical aspect rather than theoretical aspect. Therefore, there are several activi-ties such as:  (1) SurveytoSMEsinBatutraditionaldrinks, namelySMEs"Seger" and"BuRoes" and doing preliminary eva-luation(2) Designandmanufacture of mechanicalwashingmachines, machinegrater, andhydraulicpress (3) Training(4) implementing machineries in SMEs part-ner, then (5) monitoring and evaluation. Final result showed that the training mate-rial can be accepted by SMEs. The result of performance washing machine, it  obta-ined average input capacity is 5-7 kg/process/5 minutes with 95% efficiency. Grater machine performance is 5-7 kg/process/15 minutes. Moreover, the hydraulic press is the input capacity grated “empon-empon” average 3-5 kg/process/10 minutes. The benefits of this machine implemented are saving the time and power, increase production higienes, and efficiency.Keyword: grater machine, hydraulic press,rhizome washing machine,traditional drink (jamu)